Been rich all my life [videorecording (DVD)] - MacDonald, Heather (Heather Lyn); Wood, Bertye Lou; Hayes, Cleo; Ellis, Elaine, 1917-2013; Ray, Fay; Coles, Marion (First Run Features, 2006)
Meet the Silver Belles, five tap dancers who performed in 1930's Harlem at the famed Apollo and Cotton Club. Together again, they're dancing to standing ovations and sharing stories of the Harlem Renaissance.